MOTIF CERITA PADA SASTRA LISAN KALIMANTAN BARAT - NFN Musfeptial (Balai Bahasa Kalimantan Barat, 2016)
This study titled Motif story on Oral Literature of West Kalimantan. This study departs from the main issue, namely the motives on story people of West Kalimantan. Of overwhelming theories used in the study on oral literatures motif refers to the study of the theory of structuralism, which focuses on the elements of the storyline. In addition as a guide to the study of this motif is a pattern classification folklore motifs by Thomson. This study was supported methods of descriptive analysis.